A method to quantify time-dependent yield stress build-up in mineral slurries. (September 2022) - Ulrich, Dustyn; Arabi, Ameneh; Machado, Márcio B.; Martin, Thomas W.M.; Sanders, R. Sean; Kresta, Suzanne M.
Highlights: A methodology to study the build-up of the yield stress was proposed (based on rest times); A rest time of 2 min (or longer) led to an increase of yield stress. This has significantly implications for design of industrial scale stirred tanks; 45 wt% was the upper limit for assuming Newtonian rheology in our samples; Solids concentration larger than 60 wt% showed rapid build-up of yield stress and thixotropic behavior. Abstract: Mineral slurries can have very complex rheology which may not be evident in bench-scale mixing tests. On scale-up to large industrial stirred tanks, an unexpected stagnant layer sometimes forms at the surface. We hypothesize that this occurs due to build-up of yield stress when the fluid is at rest. This behavior can cause problems on scale-up, where insufficiently mixed regions of the tank contain a much larger volume of fluid and the residence time in these regions can be much longer than at the bench scale. To study this effect, a method for continuous torque measurements was developed to quantify rest time effects at the bench scale. Nickel laterite slurries (NLS) with a broad range of solids concentration (25.2–71.8 wt%) were used to test this new method. Concentric cylinder viscometry and vane rheometry were also used to measure the behavior of the test sample. Evidence for a complex mechanism of network build-up for rest times of two minutes and longer was found. Moreover, it was found that 45 wt% is the upper limit for assuming behavior which approximates Newtonian rheology in this nickel laterite slurry sample. Solids concentration greater than 60 wt% showed rapid build-up of yield stress and thixotropic behavior. The rest time experiments validated the scale-up hypothesis. The slurry concentration at which non-Newtonian behavior appears is in accordance with other rheological investigations of nickel laterite slurries.